2001
DOI: 10.1016/s0022-5347(05)66037-5
|View full text |Cite
|
Sign up to set email alerts
|

The Decompensated Detrusor V: Molecular Correlates of Bladder Function After Reversal of Experimental Outlet Obstruction

Abstract: Bladder decompensation is highly associated with a loss of sarcoplasmic reticulum function. Furthermore, the decompensated detrusor recovers function after obstruction reversal, which is associated with the recovery of these sarcoplasmic reticulum components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…A classical structure involved in calcium homeostasis is the sarcoplasmic reticulum, and PTHrP may play an important role in this calcium control. Some other studies have shown that significant changes in the sarcoplasmic reticulum after outlet obstruction produce slow and sustained increases in cytosolic calcium, which in turn lead to cellular hypertrophy via the calcineurin pathway [35,36]. It is well known that PTHrP is related to hypercalcemia, cellular proliferation and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…A classical structure involved in calcium homeostasis is the sarcoplasmic reticulum, and PTHrP may play an important role in this calcium control. Some other studies have shown that significant changes in the sarcoplasmic reticulum after outlet obstruction produce slow and sustained increases in cytosolic calcium, which in turn lead to cellular hypertrophy via the calcineurin pathway [35,36]. It is well known that PTHrP is related to hypercalcemia, cellular proliferation and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this possibility and because we were interested in examining the smooth muscle cells as directly as possible, all subsequent studies were performed using a mucosal and serosal-free preparation. It is important to note that it is well documented that partial bladder outlet obstruction induces numerous changes in contractile protein isoform, changes in expression levels of contractile regulatory proteins, and changes in calcium handling in the bladder smooth muscle cell (2,7,10,21,26,29). Thus based on the finding that the stress generation of the muscles from the two sources is similar, we interpret this to suggest that the numerous and widespread changes may be compensatory in nature and important in maintaining bladder function in the face of an obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…This is presumably due to an imbalance between the passive and active mechanical properties of the detrusor muscle and the magnitude of the resistance to flow. Removal of the obstruction before a state of severe dysfunction reverses the hypertrophic response, and normal function may be regained (7,26).…”
mentioning
confidence: 99%
“…In summary, these data suggest that despite obvious limitations of such an acute model, surgically induced pBOO can recapitulate over a shorter time frame the following essential findings observed in human beings with pBOO: (1) an increase in bladder mass, (2) an increase in voiding frequency, (3) a drop in voided volumes, (4) increased voiding pressures, (5) a significant rise in post void residual urine in a subset of these bladders, (6) upon reversal of the outlet obstruction, residual urinary frequency was seen in 30% of the rabbits [53] and (7) evidence that at the extremes of pBOO, the upper tracts begin to sense increased resting bladder pressures as manifested by the post-obstructive diuresis.…”
Section: In Vivo Measures Of Pboo In a Rabbit Modelmentioning
confidence: 99%